2019
DOI: 10.1098/rsif.2019.0214
|View full text |Cite
|
Sign up to set email alerts
|

Physics of animal health: on the mechano-biology of hoof growth and form

Abstract: Global inequalities in economic access and agriculture productivity imply that a large number of developing countries rely on working equids for transport/agriculture/mining. Therefore, the understanding of hoof conditions/shape variations affecting equids' ability to work is still a persistent concern. To bridge this gap, using a multi-scale interdisciplinary approach, we provide a bio-physical model predicting the shape of equids’ hooves as a function of physical and biological parameters. In particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…In young foals, epidermal thickness at the dorsum increases, with the greater thickness being ascribed to an increase in inter-tubular horn rather than an increase in tubule number or size. Pressure within the interpapilliary space stimulates even hoof growth [ 49 ], which may account for the number and size of tubules becoming more similar between regions. The malleable hoof wall compresses evenly despite greater dorso-medial loading during standing.…”
Section: Discussionmentioning
confidence: 99%
“…In young foals, epidermal thickness at the dorsum increases, with the greater thickness being ascribed to an increase in inter-tubular horn rather than an increase in tubule number or size. Pressure within the interpapilliary space stimulates even hoof growth [ 49 ], which may account for the number and size of tubules becoming more similar between regions. The malleable hoof wall compresses evenly despite greater dorso-medial loading during standing.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, complex proteins such as collagen and elastin participate in the formation of ECM structure, contributing to the elasticity of spheroids. It was reported that typical elastic modulus of single cells in spheroids is approximately 103 Pa (64), which is far softer than 2D culture condition. Cell communication and signal transduction in spheroids are also closer to in vivo condition than in 2D culture.…”
Section: Spheroid Culture Creates a Natural Physiological Microenviro...mentioning
confidence: 97%
“…Hoof disease is a common surgical disease in equine animals and cattle, with a higher incidence in dairy cattle [1]. In the past, cattle and horses, as the main livestock workforce, often suffered from hoof disease due to changes in the normal structure of the hoof, caused by heavy weight bearing and overwork [2,3]. Hoof disease is influenced by a number of factors, including genetics, physiological abnormalities, shed hygiene, feeding management, mechanical injuries, and infections by pathogenic bacteria, as well as feed ratios and metabolic diseases in cows [4].…”
Section: Introductionmentioning
confidence: 99%